Elaborated Study on Loan Size and Its Determinants as Critical Growth Factors for Rural Farmers in Imo State, Southeast Nigeria - Onyeagocha, S. U. O. (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
This study analyzed the loan demand requirements of rural staple and poultry farmers in Owerri Agricultural Zone of Imo State, Nigeria. Also, the factors affecting loan size were analyzed. In carrying out this cross-sectional study, data were collected with stratified sampling technique, using structured and pre-tested questionnaires from 100 loan beneficiaries and five financial institutions in the zone. The study lasted for a period of six months, effective April, 2010. Expect value method was used to determine their optimum loan requirement while OLS multiple regression analysis technique was employed in determining factors affecting loan size of beneficiaries. Results showed that the potent factors affecting loan size were farm size, level of education, enterprise type, farmers experience and dependency ratio. The result further indicated that the respondents were highly limited by capital as the financial institutions met only 60% of their capital needs. The optimum loan requirement determined for the farmers were N292, 315, and N435, 753 for Cassava and Yam farmers respectively, for farm size of 0.80 hectare. For poultry farmers of about 120 birds, the optimum loan requirement estimated was N492, 500. These figures would serve as reference points for financial institutions in loan administration of farmers of similar status and area. The financial institutions were admonished to consider providing start-up capital for the youths and fresh graduates, who apparently are yet to make in-road into farming as a business. On the other hand, government was urged to provide fiscal and monetary incentives to financial institutions supporting agriculture in view of the delicate nature of farm business. It is only discrete to note that food security should be accorded the same priority as defense as it is capable of triggering off internal and external disequilibria in terms of price fluctuation, balance of payment deficits resulting from huge importation bills, risk of hunger, mal-nutrition, social and political upheavals or conflicts. To restore normalcy and material losses encountered in such situation could require doubling the budgetary provisions on military defense.